An Oddi tumor case treated by endoscopic papillectomy - , Fatih HİLMİOĞLU, Murat ALADAĞ, Vildan TAŞKIN, Melih KARINCAOĞLU, Bülent MİZRAKİ, Bülent YILDIRIM (Turkish Journal of Gastroenterology 1, 2019)
-